IMPLEMENTASI 7 POE ATIKAN SEBAGAI STRATEGI PENDIDIKAN KARAKTER DI PURWAKARTA DALAM PEMBELAJARAN ABAD 21 - Sya'bani, Yahya Rafi; Fariha Nadhira Lutfia; Hilma Fauziah; Dellisa Ahyani; Tamara Noviani Fijia Suchi; Vini Febrianty; Afridha Laily Alindra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Purwakarta local government launched the character education program "7 Poe Atikan Pendidikan Purwakarta Istimewa" in response to the increasingly contrasting moral degradation due to the advancement of the times. In the context of 21st-century learning, character education is crucial for equipping students to develop adaptive, collaborative, and globally competitive life skills, without losing their identity and local wisdom. This research focuses on the correlation of the implementation of 7 Poe Atikan in the context of 21st-century learning. The main objective of this research is to expose the implications of implementing the 7 Poe Atikan on 21st-century skills, which include critical thinking, creativity, communication & collaboration, and digital literacy. The research method used was qualitative case study with instruments such as observation, interviews, and questionnaires. The results show that the 7 Poe Atikan program has a significant impact on shaping students' character by 96.7%. In addition, the 7 Poe Atikan program can serve as a medium for developing 21st-century skills by up to 80%. In other words, 7 Poe Atikan can develop 21st-century competencies through the integration of cultural values, character development, and the enhancement of collaborative skills and creativity among students.